Z-DNA forming regions in the human genome - Fujimoto, Y.; Schonbach, C. (Nazarbayev University, 2014)
Z-DNA is the left-handed helical structure of the usually right-handed B-DNA double helix structure. Z-DNA conformations have been found to cause mutagenesis and genetic instability [1]. In this study, human genome sequences potentially forming Z-DNA regions (ZDRs) were extracted and analysed for functional implications.
Keywords: Z-DNA; human genome; gene ontology; chromosomes